Effects of acute‐liver‐failure‐plasma exposure on hepatic functionality of HepaRG‐AMC‐Bioartificial Liver. (7th February 2013) - Nibourg, Geert A. A.; Hoekstra, Ruurdtje; van der Hoeven, Tessa V.; Ackermans, Mariëtte T.; Hakvoort, Theodorus B. M.; van Gulik, Thomas M.; Chamuleau, Robert A. F. M.
Abstract Background & Aims The AMC‐bioartificial liver loaded with the human hepatoma cell line HepaRG as biocomponent (HepaRG‐AMC‐BAL) has recently proven efficacious in rats with acute liver failure (ALF). However, its efficacy may be affected by cytotoxic components of ALF plasma during treatment. In this study, we investigated the effects of ALF‐plasma on the HepaRG‐AMC‐BAL. Methods HepaRG‐AMC‐BALs were connected to the blood circulation of rats with total liver ischaemia, either during the first 5 h after induction of ischaemia (mild ALF group), or during the following 10 h (severe ALF group). After disconnection, the BALs were assessed for cell leakage, gene transcript levels, ammonia elimination, urea production, cytochrome P450 3A4 activity, apolipoprotein A 1 production, glucose and amino acid metabolism. Results Cell leakage increased 2.5‐fold in the severe ALF group, but remained limited in all groups. Hepatic gene transcript levels decreased (max 40‐fold) or remained stable. In contrast, hepatic functions increased slightly or remained stable. Particularly, urea production increased 1.5‐fold, with a concurrent increase in arginase 2 transcription and arginine consumption, with a trend towards reduced conversion of ammonia into urea. The amino acid consumption increased, however, the net glucose consumption remained stable. Conclusions The HepaRG‐AMC‐BAL retains functionality after both mild and severe exposure to ALF plasma, but urea production may be increasingly derived from arginase 2 activity instead of urea cycle activity. Nevertheless, the increase in cell leakage and decrease in various hepatic transcript levels suggest that a decrease in hepatic functionality may follow upon extended exposure to ALF plasma.